Coupling Hybrid Energy Storage System to Regenerative Actuators in a More Electric Aircraft: Dynamic Performance Analysis and CO2 Emissions Assessment concerning the Italian Regional Aviation Scenario. (January 2022) - Barelli, L.; Bidini, G.; Ottaviano, P.A.; Gallorini, F.; Pelosi, D.
Highlights: regenerative Electro-Mechanical actuators employed for flight control surface. hybrid LiFePO4 battery/supercapacitor energy storage system is coupled to EMAs. A proper management strategy is developed aiming to reduce battery solicitations. 79% reduction in ESS weight thanks to hybridization with respect to battery system. fuel and CO2 emissions savings are assessed. Abstract: Considering an estimated growth rate by four percent per year for commercial and passengers airline to date, the aircraft industry is looking for new solutions in order to meet new stringent policies aimed at the greenhouse gases and pollutants reduction. In such framework, the concept of a More Electric Aircraft has been developing in order to introduce electrical systems for energy recovery and storage on-board. In this paper, a dynamic model of a hybrid energy storage system composed by a LiFePO4 battery and a supercapacitor, coupled to eight regenerative electro-mechanical actuators (r-EMAs) employed for the flight control surface, is implemented to store recovered energy and to drive r-EMAs. A proper management strategy is developed aiming to reduce battery solicitations, imposing a discharge at constant rate to maintain supercapacitor state of charge within the operating limits. Therefore, the instantaneous power demand/generation by the actuators is totally managed by the supercapacitor, due to its high power to capacity ratio and very long lifespan. Such strategy allows, with respect to the case of a not hybrid storage section constituted by a LiFePO4 battery, to reduce the storage section weight, extend battery lifetime since dangerous power spikes are accomplished by the supercapacitor, as well as recover energy thanks to the installation of the r-EMAs. Furthermore, an in-depth assessment is carried out in reference to the Italian «regional airline» scenario. In detail, the reduction of carbon dioxide emissions, associated with the weight saving and energy recovery introduced by HESS coupling to the regenerative actuators, has been evaluated with respect to conventional non-regenerative EMAs driven by a LiFePO4 battery. The analysis has been conducted for the single aircraft and for the estimated fleet for Italian national flights over a long term operating scenario and compared to the CO2 emissions produced in Italy by power generation, in order to quantify the benefits inherent to a massive introduction of such a system in air fleets.